SGLT2 inhibitors improve kidney function and morphology by regulating renal metabolic reprogramming in mice with diabetic kidney disease - Lu, Yong-Ping; Zhang, Ze-Yu; Wu, Hong-Wei; Fang, Li-Jing; Hu, Bo; Tang, Chun; Zhang, Yi-Qing; Yin, Lianghong; Tang, Dong-E.; Zheng, Zhi-Hua; Zhu, Ting; Dai, Yong (Journal of translational medicine, 2022)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease (ESRD) worldwide. SGLT2 inhibitors are clinically effective in halting DKD progression. However, the underlying mechanisms remain unclear. The serum and kidneys of mice with DKD were analyzed using liquid chromatography with tandem mass spectrometry (LC–MS/MS)-based metabolomic and proteomic analyses. Three groups were established: placebo-treated littermate db/m mice, placebo-treated db/db mice and EMPA-treated db/db mice. Empagliflozin (EMPA) and placebo (10 mg/kg/d) were administered for 12 weeks. EMPA treatment decreased Cys-C and urinary albumin excretion compared with placebo by 78.60% and 57.12%, respectively (p < 0.001 in all cases). Renal glomerular area, interstitial fibrosis and glomerulosclerosis were decreased by 16.47%, 68.50% and 62.82%, respectively (p < 0.05 in all cases). Multi-omic analysis revealed that EMPA treatment altered the protein and metabolic profiles in the db/db group, including 32 renal proteins, 51 serum proteins, 94 renal metabolites and 37 serum metabolites. Five EMPA-related metabolic pathways were identified by integrating proteomic and metabolomic analyses, which are involved in renal purine metabolism; pyrimidine metabolism; tryptophan metabolism; nicotinate and nicotinamide metabolism, and glycine, serine and threonine metabolism in serum. In conclusion, this study demonstrated metabolic reprogramming in mice with DKD. EMPA treatment improved kidney function and morphology by regulating metabolic reprogramming, including regulation of renal reductive stress, alleviation of mitochondrial dysfunction and reduction in renal oxidative stress reaction.